Auditing in the blockchain: a literature review - Zhang, Yunfan; Ma, Zifei; Meng, Jiaming (Frontiers in Blockchain, 2025)
This investigation evaluates blockchain’s dichotomous effects on auditing through systematic literature synthesis and comparative case studies of Big Four accounting firms. Empirical evidence demonstrates that distributed ledger technology enhances audit efficacy through automated transaction authentication (exemplified by PwC’s 90% temporal reduction in reconciliation protocols) and machine learning-powered anomaly detection algorithms, enabling comprehensive audit sampling and continuous monitoring capabilities. Persistent technical risks remain, notably 51% consensus vulnerabilities, self-executing contract exposures, and throughput constraints in decentralized architectures, which collectively compromise system integrity. Furthermore, regulatory lacunae in cross-jurisdictional compliance frameworks and practitioners' competency deficits in cryptographic validation techniques substantially impede technological assimilation. The analysis substantiates three critical imperatives: (1) harmonized regulatory frameworks with Turing-complete compliance protocols, (2) cross-disciplinary human capital development initiatives, and (3) applied research on heterogeneous system interoperability. Strategic mitigation of these implementation barriers could transition auditing toward cryptographic trust ecosystems, contingent upon synergistic collaboration between regulatory bodies establishing adaptive governance models, corporate entities developing hybrid audit architectures, and academic institutions advancing validation methodologies.